DEVELOPMENT OF RECOMBINANT PETASE ENZYME IN ESCHERICHIA COLI BL21 (DE3) - Stevensen, Jansen
Polyethylene terephthalate (PET) is a widely used plastic due to its affordability, lightweight nature, and strength. However, the extensive utilization of PET has resulted in a significant environmental concern due to its resistance to natural degradation, leading to the accumulation of plastic waste that negatively impacts the environment. In 2016, a breakthrough discovery was made with the identification of an enzyme called polyethylene terephthalate hydrolase (PETase) derived from the Ideonella sakaiensis bacteria. PETase has the ability to degrade PET, offering potential solutions to address the environmental challenges posed by PET plastic waste. As PETase shows promise for industrial applications, previous studies have focused on developing PETase mutants with improved thermostability and activity. This study aimed to evaluate the activity of these PETase mutants, which were constructed in silico, and compare them to the wild-type PETase enzyme. The PETase gene was incorporated into the pET22b(+) vector and subsequently transformed into Escherichia coli BL21 (DE3) for expression and analysis. The confirmation of transformation was performed using various techniques, including colony polymerase chain reaction (PCR), plasmid isolation, PCR of the isolated plasmids, and Sanger sequencing. These methods were employed to ensure the successful incorporation of the PETase gene into the bacterial host. Subsequently, the expression of the PETase enzyme was optimized in the extracellular fraction. This optimization process involved manipulating two key variables: the concentration of isopropyl ?-D-1-thiogalactopyranoside (IPTG) (ranging from 0 to 1.0 mM) and the duration of induction (8, 16, and 24 hours). By manipulating these parameters, the objective was to determine the optimal conditions that would maximize the expression levels of the PETase enzyme in the extracellular environment. The expression of PETase and the protein bands were detected using SDS-PAGE and analyzed using the ImageJ software. The protein products were subsequently purified using a Ni-NTA column, followed by a dialysis process. The protein was then subjected to thermostability testing, enzyme activity analysis, and western blot analysis. Crude and purified PETase activities were evaluated using analog substrates, specifically p-nitrophenyl butyrate (p-NPB) and PET sheets. The study demonstrated the successful transformation of the PETase gene carrier vector, enabling extracellular expression through the Sec secretion pathway system in Escherichia coli BL21 (DE3). The optimal conditions for expressing the PETase wild type protein were observed at 24°C with an IPTG concentration of 1 mM and an induction duration of 16 hours. In contrast, the PETase mutant exhibited optimal expression at an IPTG concentration of 0.25 mM and an induction duration of 24 hours, with statistical significance (P<0.05). The PETase mutant enzyme exhibited enhanced thermostability with an increased melting temperature (Tm) of 15.7°C, reaching 66°C. It demonstrated optimal activity at 60°C and displayed superior activity and thermostable properties compared to the wild type. The catalytic activity of the PETase wild type enzyme on PET resulted in the formation of a pore with a diameter of 9.87 ?m and an area of 26.332 ?m2. Conversely, the PETase mutant formed a larger pore with a diameter of 12 ?m and an area of 70,844 ?m2. In conclusion, the confirmed PETase mutant enzyme exhibits improved thermostability and superior catalytic activity compared to the wild-type PETase. This research on PETase enzyme development holds the potential to advance PET plastic waste treatment and contribute to the production of "zero waste" products.